2017
DOI: 10.1038/srep45047
|View full text |Cite
|
Sign up to set email alerts
|

HDAC1-3 inhibitor MS-275 enhances IL10 expression in RAW264.7 macrophages and reduces cigarette smoke-induced airway inflammation in mice

Abstract: Chronic obstructive pulmonary disease (COPD) constitutes a major health burden. Studying underlying molecular mechanisms could lead to new therapeutic targets. Macrophages are orchestrators of COPD, by releasing pro-inflammatory cytokines. This process relies on transcription factors such as NF-κB, among others. NF-κB is regulated by lysine acetylation; a post-translational modification installed by histone acetyltransferases and removed by histone deacetylases (HDACs). We hypothesized that small molecule HDAC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

9
56
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 65 publications
(66 citation statements)
references
References 57 publications
9
56
0
Order By: Relevance
“…Thus, MS-275 gives rise to either pro-or anti-inflammatory effects in these cells. In line with this, we demonstrated that MS-275 gives rise to mixed effects on pro-and anti-inflammatory gene expression in RAW264.7 macrophages with upregulation of both pro-and antiinflammatory genes [71]. Importantly, MS-275 increased anti-inflammatory IL10 expression, and we identified NF-κB as a regulator.…”
supporting
confidence: 64%
See 4 more Smart Citations
“…Thus, MS-275 gives rise to either pro-or anti-inflammatory effects in these cells. In line with this, we demonstrated that MS-275 gives rise to mixed effects on pro-and anti-inflammatory gene expression in RAW264.7 macrophages with upregulation of both pro-and antiinflammatory genes [71]. Importantly, MS-275 increased anti-inflammatory IL10 expression, and we identified NF-κB as a regulator.…”
supporting
confidence: 64%
“…This mechanism is in line with literature that describes that LPS stimulation of macrophages activates NF-κB, which induces the expression of IL10 along with TNFα, IL1β and IL12b [72], which is further enhanced by MS-275 in our study. Upon testing MS-275 in a mouse COPD (cigarette smoke exposure) model, anti-inflammatory effects were observed on several parameters including increased anti-inflammatory IL10 expression in lung macrophages, reduced KC (murine IL-8) expression and reduced neutrophilic influx upon MS-275 treatment, which is the first time that anti-inflammatory effects of an HDACi are being reported in a COPD mouse model [71].…”
mentioning
confidence: 99%
See 3 more Smart Citations